Greenhouse Manufacturers and Suppliers - George J. Hochmuth; Robert C. Hochmuth (EDIS)
Revised! HS-1020, a 6-page fact sheet by George J. Hochmuth and Robert C. Hochmuth, provides a partial directory of greenhouse manufacturers and suppliers. Published by the UF Department of Horticultural Sciences, February 2009.